SURGICAL TREATMENT OF FRACTURES OF THE NECK AND DIAPHYSIS OF THE FEMUR - Tukhtaev J.T.; Mamadzhanov K.H.; Botirov N.T.; Jalilov F.R.; Abdulazizov O.N. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
17 patients with fractures of the femoral neck and diaphysis were operated on. Fractures were obtained as a result of high-energy trauma, accompanied by multiple and combined injuries. When planning and performing internal osteosynthesis, anatomical and physiological features of the proximal femur, localization and type of cervical fracture according to Pauwels, the nature of the diaphyseal fracture, the condition of the surrounding soft tissues were taken into account.